Dynamic simulation and aircraft level assessment of CMC implementation on GTF engine - Mo, Da; Roumeliotis, Ioannis; Liu, Yixiong; Mourouzidis, Christos; Kissoon, Sajal (Springer, 2023)
This paper dynamically simulated the geared turbofan engine with CMC turbine components, including impacts of fuel schedule, shaft inertia, volume packing, BOV schedule. Deliberated comparisons were performed between CMC engine and Inconel engine on aircraft level performance and transient behaviour. Heat load examination is included in flight mission analysis, which lays the basis on the gearbox efficiency map related to torque and rotational speed. Results indicate that IPC surge margin of the CMC case slightly fall 0.15% but maintain steady. The mitigated T4 overshooting phenomenon has offered a 30 K drop and thus extended turbine life. More importantly, Fan shaft inertia dominantly affects engine operability, whereas the blow-off air fraction severely impacts the low power setting operation. Further investigation of heat load reveals that power loss at take-off segment accounts for 1.1% of IP shaft input power, which is 3.98% higher than Inconel case. The thermal management system needs to be redesigned to absorb extra heat. On assessment of aircraft level performance, CMC engine provides superior profits in maximizing airline revenue. The predicted annual fuel cost saving is about 0.08 million dollars coming from block fuel reduction. NOx, noise and CO2 demonstrate obvious decline, approaching 5.9%, 1.0% and 4.9%, respectively.
Keywords: CMC; Aircraft level performance; Transient performance; Heat load; Emissions